Factors of a Successfully Implemented Compulsory Settlement - Marjeta Zorin Bukovšek; Borut Bratina; Polona Tominc (Naše gospodarstvo/Our economy, 2017)
In Slovenia, many companies try to avoid bankruptcy with the introduction of a compulsory settlement procedure, but only a handful of companies successfully complete the compulsory settlement in the sense of a final repayment of creditors in accordance with the adopted financial restructuring plan. The article identified the factors affecting the confirmation of a compulsory settlement as well as the factors affecting the final repayment of creditors and, thus, permanently eliminated the causes of insolvency. The factors were divided into internal and external, whereby the impact of factors on a successfully completed compulsory settlement was verified using quantitative and qualitative research methods.